Expression and functional characterization of a C-7 cholesterol desaturase from Tetrahymena thermophila in an insect cell line - Poklépovich Caride, Tomás Javier (2015)
Tetrahymena thermophila transforms exogenous cholesterol into pro-vitamin D3 (7-dehydrocholesterol) with remarkable efficiency in a one-step reaction carried out by a C-7 cholesterol desaturase. The enzyme DES7 is encoded by the gene TTHERM-00310640, identified with RNAi and gene knock-out experiments, but has not yet been heterologously expressed actively in any organism. A model derived from its amino acid sequence classified DES7p as a Rieske-type oxygenase with transmembrane localization. The protein has catalytic activity, sequence and topological similarity to DAF-36/Neverland proteins involved in the synthesis of steroid hormones in insects and nematodes. Due to their structural and functional similarity, we analyzed the expression of a codon optimized DES7 gene from Tetrahymena in the insect Sf9 cell line, identified and measured the steroid metabolites formed, and extended the actual knowledge on its localization. We found that the accumulation of 7-dehydrocholesterol could be increased 16-40-fold in Spodoptera frugiperda, depending on physiological conditions, by overexpression of T. thermophila DES7. The protein was detected in the microsomal fraction, in accordance with previous reports. Although the electron transfer chain for Des7p/DAF-36/Neverland Rieske-type oxygenases is presently unknown, we identified possible donors in the ciliate and insect genomes by bioinformatic analysis. In spite of the large evolutionary distance between S. frugiperda and T. thermophila, the results indicate that there is significant functional conservation of the electron donors, since the ciliate's sterol desaturase can function in the context of the insect electron transport system. The results achieved demonstrate that DES7 is the first gene from a ciliate, coding for a microsomal enzyme, expressed in active form in an insect cell line.